ORGANISASI MASYARAKAT ISLAM AL-JAMIYATUL WASHILIYAH - muhajir muhajir (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
The basic activity of Al-Washliyahin social and state are speech, and social aspect, its can see in the resulty of the hard work in every sub devision in social culture. Al-washilyah born in Colonial of Belanda era. In this era the spirit to be unity come and rise in the society. In our country was born the other organization such as: Budi Utomo, Syarikat Islam, Muhammadiyah, Nahdhatul Ulama and other organizations. In East Sumatra many boarding house had build. Rumah suluk, studi of Islam, group of Islam followers come and rise in every where in East Sumatra.